The role of tourist engagement in mediating the influence of digital storytelling and accessibility on tourists' visiting decisions to Aek Sijorni - Nurdyanti Choirunnisa Pane; M Ikhsan Harahap; Faisal Umardani Hasibuan (Institute of Accounting Research and Novation (IARN), 2026)
This study aims to analyze the influence of digital storytelling and accessibility on the decision to visit the Aek Sijorni tourist attraction, with visitor engagement as a mediating variable. The study used a quantitative approach using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. Data were obtained through questionnaires distributed to domestic tourists and potential visitors. The results indicate that digital storytelling does not have a direct, significant effect on the decision to visit, but has a positive and significant effect on tourist engagement. Accessibility has a positive and significant effect on both tourist engagement and the decision to visit. Tourist engagement also has a positive and significant effect on the decision to visit. The results of the mediation test indicate that tourist engagement partially mediates the relationship between accessibility and the decision to visit, and fully mediates the relationship between digital storytelling and the decision to visit. These findings emphasize the important role of tourist engagement in driving the decision to visit. The implications of this research suggest that destination managers need to improve accessibility and develop digital storytelling that can enhance tourist engagement to encourage increased visits.